PEMBELAJARAN GEOGRAFI SISTEM DARING DI SMA N 1 HABINSARAN - Neny Widya. N Pane; Yurni Suasti (JURNAL BUANA, 2021)
SMAN 1 Habinsaran is a school in the district. Habinsaran, Kab. Toba, North Sumatra which applies a bold learning system. The conditions obtained are the applications used by the geography teacher at SMAN 1 Habinsaran are wa group, quipper and zoom. The application used is not in accordance with the application suggested by the principal, namely not using GCR because it does not understand GCR and the geography teacher does not have teaching materials to be uploaded to the geolge classroom. Geography teacher is only part of the features of the application used. Quipper's unknown features in the settings, announcements and code because it's written in English so it's difficult to understand the meaning. Application usage is still not optimal. The advantages of using online applications are being able to send messages, convey material boldly, communicate with students, and be able to assess and process grades. The drawbacks of online applications that are used at SMAN 1 Habinsaran are an unstable network, limited internet quota and adequate Android.